Pengaruh Model Teaching at the Right Level (TaRL) terhadap Kemampuan Menyajikan Teks Deskripsi Secara Lisan - Shafira Nur Alifah; Khaerunnisa Khaerunnisa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study was motivated by the low ability of seventh grade students at SMP Dharma Karya UT to present descriptive texts orally, which is indicated by their lack of fluency, unclear pronunciation and intonation, and low self-confidence. This condition is aggravated by monotonous learning models that make students feel bored. One alternative to overcome this problem is the application of the Teaching at The Right Level (TaRL) learning model. This model focuses on the students’ actual ability levels so that the content and learning activities can be adjusted to their readiness to learn. This research used a quantitative method with a Randomized Demonstration Group Posttest Only Design and involved two groups: an experimental class and a control class. The sample consisted of 53 seventh grade students of SMP Dharma Karya UT. The research instrument was a test of oral descriptive text presentation skills. The results show a significant effect of applying the TaRL model on students’ ability to present descriptive texts orally. The experimental class receiving TaRL obtained an average posttest score of 47.8 out of 80, while the control class only scored 34.29 out of 80. The t-test showed tcount (2.45) > ttable (1.66) at a 5% significance level, so H0 was rejected and H1 was accepted. It can therefore be concluded that the application of the TaRL model is more effective than conventional teaching in improving students’ oral presentation skills of descriptive texts.